Learning styles preferences and e-learning experience of undergraduate dental students - Ana Cláudia DALMOLIN; Giselle Ariana Otto MACKEIVICZ; Márcia Thaís POCHAPSKI; Gibson Luiz PILATTI; Fábio André SANTOS
Abstract Introduction Education in the health sciences has been undergoing profound changes due to the incorporation of information and communication technologies. Students learn through a variety of approaches, according to their learning styles. Blended learning, which combines technology-aided learning (e-learning) with traditional face-to-face teaching methods, has been found to improve learning outcomes. Objective The aims of the present study were to evaluate the learning styles of undergraduate dental students and their experience towards the use of e-learning. Material and method Two electronic questionnaires were sent to 174 students. The learning styles were determined by the Felder & Soloman Index (ILS), which evaluates the following four dimensions of learning: processing information (active-reflexive); perceiving information (sensorial-intuitive); receiving information (visual-verbal); and understanding information (sequential-global). To determine the e-learning experience we used four questions (Likert scale - five-point) which addressed the experience and the use of information and communication technologies. Result Most students presented a well-balanced style for the active-reflective (60%) and sequential-global (68%) domains. The sensing style (64%) was predominant. A lower percentage presented a global characteristic (9%). We did not find significant differences regarding the age groups (19-21 and 22-33 years) and genders (P>0.05, χ 2). However, in terms of age the difference was significant concerning websites helping in learning (P=0.0363, Mann-Whitney). Conclusion We conclude that the students do not have the same learning styles and e-learning experience. Methods such as blended learning could provide advantages when teaching undergraduate dental students.